Analisis Growth Mindset Mahasiswa dalam Challenge-Based Learning Berbasis Deep Learning - Lina Marlina (Integralistik, 2026)
This study examines the relationship between university students' growth mindset and their engagement in Challenge-Based Learning (CBL) supported by a deep learning approach. A quantitative approach with a descriptive correlational design was employed involving 85 undergraduate students selected through purposive sampling. Data were collected using validated and reliable Likert-scale questionnaires and analyzed through descriptive statistics and Pearson correlation analysis. The findings reveal that students demonstrated a high level of growth mindset (M = 4.12) and student engagement (M = 4.05). Furthermore, a positive and statistically significant relationship was identified between growth mindset and student engagement (r = 0.68, p < 0.05), indicating that students with stronger growth mindsets tend to participate more actively, collaborate more effectively, and engage more deeply in challenge-based learning activities. These findings suggest that integrating Challenge-Based Learning with a deep learning approach promotes meaningful, reflective, and student-centered learning experiences. This study contributes to the literature by providing empirical evidence for an integrative pedagogical framework that positions growth mindset as a psychological foundation, Challenge-Based Learning as an instructional strategy, and the deep learning approach as a mechanism for strengthening student engagement. This framework offers a comprehensive perspective for designing innovative and meaningful learning in higher education.